WHO HELPS TO GIVE BIRTH TO MATEUS? THE MATERNITY OF CANVASES/TENTS OF BOA VISTA/RR (ESMAT Magazine, 2025)
This study was carried out as part of the Postgraduate Programme in Societyand the Border (PPGSOF) at the Federal University of Roraima (UFRR). This researchfocused on analyzing obstetric violence experienced by pregnant women, parturients andmothers in the city of Boa Vista - RR. The methodology used was qualitative, descriptive andbibliographical, based on an intersectional feminist epistemology, Gender and History. Thegeneral objective was to analyze obstetric violence in the state of Roraima caused by non-compliance with Women's Fundamental Rights, addressing the situation at the Nossa Senhorade Nazareth Maternity Hospital, which, at the time of the research, was operating in atemporary structure made up of tarpaulins and tents. The specific objectives includedpresenting the case of the tarpaulin/tent maternity hospital in Boa Vista/RR andconceptualizing Obstetric Violence with a focus on gender-based violence. The researchsought to investigate the causes and forms of obstetric violence, promoting debate in themedical and legal spheres on the formulation of preventive standards and civil, criminal andadministrative liability. It also correlated the understanding of obstetric violence and powerrelations, considering gender inequality in the context of the Nossa Senhora de Nazarethmaternity hospital. The study emphasized respect for women's rights, assessing the forms ofabuse of power, since in some cases health professionals used their authority to imposeinvasive or unnecessary practices, disregarding women's wishes and needs. In this respect, theresearch highlighted the influence of patriarchal structure and pointed to the need for an in-depth study on the subject. It also included an investigation into the need for humanization inobstetric care, considering that this can be marked by a lack of empathy and welcome forwomen, generating fear, insecurity and trauma. The results obtained during the research wereconsidered fundamental for the construction of effective public policies that safeguard thefundamental rights of women in Roraima and guarantee access to dignified and adequatehealth care. The preliminary results indicate the existence of obstetric violence against womenin the state of Roraima.
Keywords: Obstetric Violence; Women`s Rights; Women´s Health in Roraima